The effects of temperature on prevalence of facultative insect heritable symbionts across spatial and seasonal scales - Martins, Marcos; César, Cássia Siqueira; Cogni, Rodrigo (Frontiers in Microbiology, 2023)
Facultative inheritable endosymbionts are common and diverse in insects and are often found at intermediate frequencies in insect host populations. The literature assessing the relationship between environment and facultative endosymbiont frequency in natural host populations points to temperature as a major component shaping the interaction. However, a synthesis describing its patterns and mechanistic basis is lacking. This mini-review aims to bridge this gap by, following an evolutionary model, hypothesizing that temperature increases endosymbiont frequencies by modulating key phenotypes mediating the interaction. Field studies mainly present positive correlations between temperature and endosymbiont frequency at spatial and seasonal scales; and unexpectedly, temperature is predominantly negatively correlated with the key phenotypes. Higher temperatures generally reduce the efficiency of maternal transmission, reproductive parasitism, endosymbiont influence on host fitness and the ability to protect against natural enemies. From the endosymbiont perspective alone, higher temperatures reduce titer and both high and low temperatures modulate their ability to promote host physiological acclimation and behavior. It is necessary to promote research programs that integrate field and laboratory approaches to pinpoint which processes are responsible for the temperature correlated patterns of endosymbiont prevalence in natural populations.